2001
DOI: 10.1164/ajrccm.163.4.2005022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Edentulism on Spirometric Tests

Abstract: The impact of denture wear in edentulous subjects while performing routine spirometric measurements has never been systematically investigated. We compared the values of FVC, FEV(1), PEFR, FEF(50%), FIV(1), and FIF(50%) recorded with and without dentures in three groups of edentulous subjects: 36 asymptomatic subjects with normal spirometry (N), 22 patients with chronic obstructive pulmonary disease (COPD), and 18 with interstitial lung disease (ILD). In 14 subjects retropharyngeal space with and without dentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 4 publications
1
35
1
6
Order By: Relevance
“…Reducing the effort partway through the manoeuvre [13] may give a higher expiratory volume in some subjects, but then is no longer a maximally forced expiration. Well-fitting false teeth should not be routinely removed, since they preserve oropharyngeal geometry and spirometry results are generally better with them in place [14].…”
Section: Test Proceduresmentioning
confidence: 99%
“…Reducing the effort partway through the manoeuvre [13] may give a higher expiratory volume in some subjects, but then is no longer a maximally forced expiration. Well-fitting false teeth should not be routinely removed, since they preserve oropharyngeal geometry and spirometry results are generally better with them in place [14].…”
Section: Test Proceduresmentioning
confidence: 99%
“…Forced mid-inspiratory flow (FIF 50 ) was used as the arbitrary index of upper aiway patency [7], as we previously found that it is mostly influenced by removing dentures [6]. Predicted values for FIF 50 were obtained in our laboratory, from a population of 75 asymptomatic healthy subjects without OSA, matched for age and sex.…”
Section: Methodsmentioning
confidence: 99%
“…Very few studies were carried out to evaluate the effect of wearing complete dentures in edentulous patients on spirometric readings. 7 The subjects selected for this study were normal edentulous patients and the fabrication of complete dentures using standard conventional method and routine materials provided a homogenous and representative sample. The clinical material used in study consisted of both male and female patients.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in mean PIFR might be due to increase in retropharngeal space after wearing complete dentures and are in agreement with the findings of previous studies. 7,8 Pellegrino R, Viegi G, Brusasco V, et al have also concluded that maximum inspiratory flow (PIF) is largely decreased with an extrathoracic airway obstruction, because the pressure surrounding the airways (which is almost equal to atmospheric) cannot oppose the negative intraluminal pressure generated with the inspiratory effort. 9 In contrast, it is little affected by an intrathoracic airway obstruction.…”
Section: Discussionmentioning
confidence: 99%